LUNG TUMOUR DETECTION USING ULTRA-WIDEBAND MICROWAVE IMAGING APPROACH - A., . R. H. Alhawari (جامعة الوادي university of eloued, 2018)
The use of Ultra-Wideband (UWB) microwave imaging for tumour detection has gained increasing popularity within the bio-medical field. Microwave imaging turned out more efficiently accurate to some body parts such as breast and brain imaging. This work presents on the possibility and the effectiveness of UWB microwave imaging technique on lung tumour detection. Simple technique of using reflection method was studied and then applied for lung tumour detection by using UWB antenna. The simulated results show that the proposed method is capable to detect a lung tumour with minimum radius size of 4 mm for different positions inside the lungs at the frequency of 3.67 GHz. It is a promising technique to be further developed in modern UWB imaging systems which demand perfect results at very low cost
artica
Keywords: ultra-wideband; microwave imaging; lung tumour; Antenna